Did the Great Inflation occur despite policymaker commitment to a Taylor rule? - James Bullard; Stefano Eusepi (Federal Reserve Bank of Atlanta, 2003)
The authors study the hypothesis that misperceptions of trend productivity growth during the onset of the productivity slowdown in the United States caused much of the great inflation of the 1970s. They use the general equilibrium, sticky price framework of Woodford (2002), augmented with learning using the techniques of Evans and Honkapohja (2001). The authors allow for endogenous investment as well as explicit, exogenous growth in productivity and the labor input. They assume the monetary policymaker is committed to using a Taylor-type policy rule. The authors study how this economy reacts to an unexpected change in the trend productivity growth rate under learning. They find that a substantial portion of the observed increase in inflation during the 1970s can be attributed to this source.
Keywords: 330; Equilibrium (Economics); Monetary policy; Macroeconomics; Inflation (Finance); Productivity